Optimizing maize growth and N dynamics in Northeast China by combining dairy cattle slurry and synthetic fertilizer - Hui Shao; Xiangyu Ma; Changzhi Jia; Junhui Liu; Fengbo Zhu; Xuebing Wu; Jiahui Duan; Xuesheng Liu; Baiwen Jiang (Crop Journal)
Dairy cattle slurry is a source of nitrogen (N) that can substitute for synthetic fertilizers. This study aimed to identify combinations of synthetic fertilizers and slurry optimal for maize growth and N dynamics in Northeast China. In a two-year field experiment testing synthetic-to-slurry N fertilization ratios, slurry application increased grain yield and yield components, net economic benefit, and N use efficiency relative to synthetic fertilization but led to higher nitrous oxide and ammonia emissions. A 1:1–1:3 synthetic N: slurry N ratio and slurry application at 60–90 t ha−1 balanced productivity with N losses.